Evaluation of analgesic and anti-inflammatory activities of the root extract of Grewia schweinfurthii Burret and its major chemical constituents - Abdi Leta Gemechu; Mirutse Giday; Solomon Tadesse; Ariaya Hymete (PLoS ONE, 2026)
Despite the widespread use of conventional analgesic and anti-inflammatory drugs, their clinical utility is often limited by adverse effects, necessitating the search for safer alternatives from medicinal plants. This study investigated the analgesic and anti-inflammatory activities of the 80% methanolic root extract of Grewia schweinfurthii Burret and an isolated bioactive compound using established rodent models. Air-dried roots were extracted by maceration with 80% methanol, and acute oral toxicity was evaluated following OECD guidelines. Analgesic activity was assessed using the acetic acid–induced writhing and hot plate models in mice, while anti-inflammatory activity was evaluated using carrageenan-induced paw edema in rats. A bioactive compound, 4 (2ʺ-(4′-isopropylphenyl) propan-2ʺ-yl)-2,3-dihydrofuran, was isolated via column chromatography and tested for anti-inflammatory activity. In the writhing test, the extract produced significant (p < 0.001) dose-dependent inhibition of abdominal constrictions, with 13.90%, 56.81%, and 75.48% inhibition at 100, 200, and 400 mg/kg, respectively, compared to 80.77% inhibition by aspirin (150 mg/kg). In the hot plate model, the 400 mg/kg dose significantly prolonged latency time from a baseline of 5.67 ± 0.33 s to 9.17 ± 1.01 s at 120 min (p < 0.05), indicating central analgesic activity. In the carrageenan-induced paw edema model, the extract demonstrated marked anti-inflammatory effects, with 93% inhibition at 400 mg/kg at the 5th hour, comparable to indomethacin (95% inhibition). The isolated compound exhibited significant dose-dependent anti-inflammatory activity, achieving 75% inhibition at 40 mg/kg at 5 hours (p < 0.001). Overall, the findings demonstrate that G. schweinfurthii root extract and its isolated compound possess significant peripheral and central analgesic as well as potent anti-inflammatory activities, supporting the plant’s traditional use; however, further mechanistic, toxicological, and pharmacokinetic studies are required before clinical relevance can be established.